Stakeholder Involvement in Post Overcoming Poverty and Unemployment Post 2018 - Hasbullah, Hasbullah; Husain, Sulfitri; Nurhamni, Nurhamni; Yogi Pratama, Muhammad; Nelpanus, Nelpanus (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Central Sulawesi has been known as one of the disaster-prone areas, especially after the 2018 disaster which resulted in liquefaction, tsunamis and earthquakes occurring simultaneously. This large-scale natural disaster caused both physical and non-physical losses, until finally the government made every effort to ensure conditions returned to normal. The government's efforts to improve infrastructure and public facilities have been realized, including improving the economic sector and providing permanent housing for disaster survivors. However, on the other hand, post-disaster causes poverty and unemployment, especially in Palu City. Even though the open unemployment rate has currently decreased from 16,960 people (2020) to 15,302 people (2021), the number of poor people in the same year has increased to reach 28,600 people compared to 26,890 people in 2020. On this basis, the post-disaster recovery process must be carried out intensively, involving various stakeholders. The aim of this research is to find out what role stakeholders play during post-disaster recovery, especially in overcoming poverty and unemployment levels in the city of Palu. Data collection techniques were carried out using interviews and documentation. Interviews were aimed at stakeholders or related agencies, including the Regional Poverty Alleviation Coordination Team (Tim Koordinasi Pengentasan Kemiskinan Daerah-TKPKD) for provinces and districts/cities throughout Central Sulawesi, P5TK for the Manpower and Transmigration Service, the Training Development Division for the Expansion of Placement and Productivity of Nakertrans Workers, as well as communities affected by the disaster. Documentation was carried out by obtaining data from journals, news and BPS reports for the city of Palu in figures for 2022. This research was carried out within one year and used quantitative descriptive methods.